Papua Problems in the Review of Constitutional Law - Triadi, Irwan (Faculty of Law, Universitas Pekalongan, 2022)
The Papua problem is a dispute in the Papua region, Indonesia. beginning in 1961. In 1962, the Netherlands agreed to relinquish the temporary UN administrative area, signing the New York Agreement, which included provisions for a referendum to be held before 1969. On August 15, 1962, the New York Agreement was obtained which contained the handover of western Papua from the Netherlands via United Nations Temporary Executive Authority (UNTEA). On May 1, 1963, western Papua returned to Indonesia. In this scientific article, the type of research used is Normative Legal Research. Normative Legal Research is a scientific research approach that aims to find the truth based on scientific logic from a normative point of view. This approach involves researching various library materials, literature, and secondary data to produce legal rules, legal principles, and other legal doctrines. The implementation of terrorist status is in accordance with Law Number 5 of 2018 concerning Amendments to Law Number 15 of 2003 concerning Stipulation of Government Regulations in Lieu of Law Number 1 of 2002 concerning Eradication of Criminal Acts of Terrorism, where every organization or person who commits massive violence can be categorized as a terrorist. Every action carried out by the Armed Criminal Group, including the Papua dispute and the birth of the Free Papua Organization, whatever the name of the organization or the people affiliated with or involved with it, is a terrorist act. The Indonesian Government's political will to deal with Papua seriously began in 1999, which was marked by President Abdurrahman Wahid giving the name Papua to replace Irian Jaya). The government also designated Irian Jaya Province as a special autonomous region, which is explicitly stated in the MPR RI Decree Number IV/MPR/1999 concerning Outlines of State Policy for 1999-2004, Chapter IV letter G, point 2. Following up on the mandate of the MPR Decree, the DPR on October 22 2001 approved and enacted Law Number 21 of 2001 concerning Special Autonomy for Papua Province